Trends and traditions in southeastern zooarchaeology - Peres, Tanya M. (Ripley P. Bullen series., 2014)
This volume is a synthesis of zooarchaeology's history in the southeast, exploring the role of animals in social and economic development and examining the current trends and methodologies used.